2009
DOI: 10.1088/1748-6041/4/2/022001
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive polymers and their applications in drug delivery

Abstract: Interest in stimuli-responsive polymers is steadily gaining increasing momentum especially in the fields of controlled and self-regulated drug delivery. Delivery systems based on these polymers are developed to closely resemble the normal physiological process of the diseased state ensuring optimum drug release according to the physiological need. Also termed 'environmental-sensitive' or 'smart', these polymers experience rapid changes in their microstructure from a hydrophilic to a hydrophobic state triggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
363
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 568 publications
(384 citation statements)
references
References 156 publications
1
363
0
2
Order By: Relevance
“…This drug delivery system is applied by means of biomimetic actuators 10 . The magnetic responsive drug delivery system is based on magnet targeted to wound site that pulls the drug towards the magnet field and it can applied to the cancer treatment 11 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug delivery system is applied by means of biomimetic actuators 10 . The magnetic responsive drug delivery system is based on magnet targeted to wound site that pulls the drug towards the magnet field and it can applied to the cancer treatment 11 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research on smart drug delivery system for the chronic wounds showed it by using stimulated responsive polymers 11 . The method can be stimulated by various environments alike; temperature, electric, magnetic fields.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since temperature is a highly important parameter in the mammalian body, temperaturesensitive hydrogels have become the most investigated smart polymers [2][3]. The majority of thermosensitive hydrogels investigated in the past decades are synthetic polymers based on poly(N-isopropylacrylamide) (PNIPA) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of thermosensitive hydrogels investigated in the past decades are synthetic polymers based on poly(N-isopropylacrylamide) (PNIPA) [2][3][4]. PNIPA hydrogels exhibit a non-linear volume phase transition (VPT) at a lower critical solution temperature (LCST) around 34 °C, which is close to the natural temperature of the human body [3,5]. On being triggered by stepwise temperature changes PNIPA can exhibit a pulsatile drug release profile [3,[6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation